Digital technologies for climate action, disaster resilience, and environmental sustainability. (Asian Development Bank, 2021)
It provides an overview of the available technology types and their applications and assesses opportunities and barriers for their uptake. The publication provides insights on how digital technologies can be operationalized in the Asian Development Banks developing member countries, including to support nationally determined contributions and green recovery efforts.